2011
DOI: 10.1111/j.1574-6941.2011.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil factors exhibit greater influence than bacterial inoculation on alfalfa growth and nitrogen fixation

Abstract: In order to study the effects of soil factors and bacterial inoculation on alfalfa (Medicago sativa), plants were inoculated with Ensifer meliloti L33 and Azospirillum brasilense Sp7 in pot experiments using two different soils separately as well as in a mixture. One soil was contaminated with chemical waste products; the other was an arable soil. Soil factors, including the availability of macro- and micronutrients as well as carbon and nitrogen contents, were found to exhibit a much greater influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Soil type and farm management practices also have a great influence on rhizospheric microbe populations (Reeve et al, 2010), with nutrient availability such as N and P, different pH, moisture content varying widely across soil types, with divergent capacities to support colonisation and growth of microbes. Indeed, Neumann et al (2011) demonstrated that soil factors had a much greater influence on the growth of alfalfa than inoculation with PGP microbes. The composition of indigenous microbial communities within soils will also impact the ability of introduced microbes to effectively colonise the rhizosphere in sufficient numbers to effect plant growth (van Veen et al, 1997).…”
Section: Considerations For Use and Commercialisation Of Pgp Microbesmentioning
confidence: 98%
“…Soil type and farm management practices also have a great influence on rhizospheric microbe populations (Reeve et al, 2010), with nutrient availability such as N and P, different pH, moisture content varying widely across soil types, with divergent capacities to support colonisation and growth of microbes. Indeed, Neumann et al (2011) demonstrated that soil factors had a much greater influence on the growth of alfalfa than inoculation with PGP microbes. The composition of indigenous microbial communities within soils will also impact the ability of introduced microbes to effectively colonise the rhizosphere in sufficient numbers to effect plant growth (van Veen et al, 1997).…”
Section: Considerations For Use and Commercialisation Of Pgp Microbesmentioning
confidence: 98%
“…It can happily grow on marginal, poorly fertile sandy loam land, almost exclusively under rain-fed conditions in areas of low rainfall without any chemical or biological fertilizer. Soil factor exert greater influence than bacterial inoculation on plant growth, nitrogen fixation and nutrient uptake of plant (Neumann et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In supplement, being a mandatory element of human food and animal feed, chickpea also take part in a pivotal role in sustain soil productiveness up to 35 kg N ha -1 [2]. It has the probable to grow well in poor soils as well as to ameliorate them because of its systematic N fixation system [3]. Chickpea economize nitrogen utilization for succeeding cereal crop to the tune of 56-68 kg N ha -1 [4], which is one of the elevated among pulses [5].…”
Section: Introductionmentioning
confidence: 99%